Pandemic in the complexity of the Digital Era: How online media in Indonesia construct the reality of COVID-19 - Wahyuni, H.I. (Pacific Media Centre, Auckland University of Technology, 2022)
This article aims to examine the reality of the COVID-19 pandemic constructed by online media outlets in Indonesia as one of the primary sources of information during the crisis. It uses qualitative content analysis to determine how online media in Indonesia construct the reality of COVID-19. The countryâs eight most accessed online media websites are the objects of this study with a three-unit analysis: context, message, and tone. The result shows that Indonesian media coverage has predominantly emphasised the pandemicâs political context over the health and economic context. Inform-ants have predominantly been politicians; epidemiologists and scientists have been given little space. In this case, the media system in Indonesia through online news media were not able to play an optimal role in the early phases of the pandemic due to the tendency of this news construction. Â© 2022, Pacific Media Centre, Auckland University of Technology. All rights reserved.